Taken - Crais, Robert (New York : G.P. Putnam's Sons, 2012)
Hired along with Joe Pike to investigate the allegedly kidnapped missing daughter of a woman, Elvis Cole goes undercover to infiltrate a ring of professional border kidnappers only to be abducted himself.
Keywords: Pike, Joe (Fictitious character) -- Fiction; Cole, Elvis (Fictitious character) -- Fiction; Private investigators -- California -- Los Angeles -- Fiction; Kidnapping -- Fiction; Human trafficking -- Fiction; Mexican-American Border Region -- Fiction; Mystery fiction; Suspense fiction